PENGEMBANGAN INSTRUMEN FORMATIF TWO-TIER MULTIPLE CHOICE BERBASIS HOTS MENGGUNAKAN MEDIA WORDWALL UNTUK MENGUKUR PEMAHAMAN KONSEPTUAL PADA MATERI BILANGAN DESIMAL SISWA KELAS V SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a formative assessment instrument in the form of a Higher Order Thinking Skills (HOTS)-based two-tier multiple choice using Wordwall media to measure students’ conceptual understanding of decimal numbers in grade V elementary school. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this study were 16 fifthgrade students. Data were collected through observation, interviews, questionnaires, and tests, and analyzed using both qualitative and quantitative techniques. The results showed that the developed instrument met the feasibility criteria, with material validation at 70% (valid), language validation at 93% (very valid), and media validation at 76% (valid). All 15 items were declared valid based on the Pearson Product Moment test, and the reliability test showed a Cronbach’s Alpha value of 0.84, indicating high reliability. The item analysis results revealed that most questions were in the moderate difficulty category, had good discrimination power, and effective distractors. Therefore, the developed instrument is feasible to be used as a formative assessment tool to measure conceptual understanding and identify students’ misconceptions through an interactive learning medium.